2012
DOI: 10.1016/s1001-0742(11)60860-7
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity-based assessment of the treatment performance of wastewater treatment and reclamation processes

Abstract: The reclamation and reuse of wastewater is one of the possible ways to relieve the serious fresh water resource crisis in China. Efficient reclamation treatment technologies ensure the safe reuse of reclaimed water. In order to screen out and evaluate technologies appropriate for reclamation treatment, a great deal of efforts have been brought to bear. In the present study, a toxicity-based method including a Photobacterium phosphoreum test for acute toxicity and SOS/umu test for genotoxicity, accompanied by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The only exception was the QD that used the A 2 /O + MBR process. The good removal efficiency of A 2 /O -based process could also be reported in the literatures 33,34 . For example, Shi et al .…”
Section: Resultssupporting
confidence: 72%
“…The only exception was the QD that used the A 2 /O + MBR process. The good removal efficiency of A 2 /O -based process could also be reported in the literatures 33,34 . For example, Shi et al .…”
Section: Resultssupporting
confidence: 72%
“…Biological toxicity tests are a useful tool for investigating the effects of all the bioavailable contaminants and their interactions, and they are widely used to evaluate the safety of environmental samples. Wei et al (2012) developed a simple assessment method based on the Photobacterium phosphoreum test for toxicity tests and found that it could serve as a valuable tool for evaluating wastewater reclamation processes. In this study, the same method for acute toxicity tests was used to investigate the toxicity variations in the MBR-NF and antibiotic production wastewater treatment station in the 2nd stage.…”
Section: Toxicity Removalmentioning
confidence: 99%
“…The toxicity tests indicated that both the acute toxicity and genotoxicity had great decrease after the A 2 O process. However, advanced chemical reclamation processes such as ozonation and chlorination could possibly cause toxicity increase again (Wei et al, 2012).…”
Section: Composition Of Toxicity Test Batterymentioning
confidence: 99%